The Use of Digital Media and Modes of Communication of Affected People: A Case Study of Earthquakes in East Java, Indonesia - Ida, Rachmah (2022)
Several earthquake incidents in the East Java province have resulted in numerous disadvantages such as damaged buildings and victims that were physically and emotionally wounded. The problem that has arisen in these situations is how victims of natural disasters often receive late responses and little to no information about relief efforts from authorities. Local governments and disaster relief organizations have not initiated the right method of communication to give important information toward disaster victims when information technologies have developed rapidly. The present study opt for a qualitative research design to conduct the interviews from the victims of disaster living nearby Malang and Blitar regencies of Indonesia. It examines how people living in earthquake-prone regions are communicating during the disaster using smartphones and social networking services. The findings of the research show that people living in the disaster-risk areas use mobile phones, smart-phones, and social networking services in their daily life; yet, not many of them using these devices and services to look for information about earthquakes. Although authorities have created digital channels as a source of information, it does not receive significant attention and interest of the people at risk. The problems with uneven digital media literacy and lack of resources remain unresolved. Cooperation between authorities and people is expected, to ensure that the use of existing communication technologies becomes more effective and efficient in earthquake relief efforts and countermeasures. © Fuji Technology Press Ltd.